The retina in hypertensive disorders of pregnancy: a study of the prevalence and association with severity of disease in a tertiary referral centre in India - Sharma, Jasmine C.; Choudhary, Bithi; Maru, Laxmi; Mathur, Poonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hypertensive disorders of pregnancy remains to be a major cause of maternal and fetal morbidity and mortality. The retina offers the unique opportunity to directly observe changes in the vasculature due to preeclampsia. Fundoscopy can be used to prognosticate and assess the severity of disease and offer an optimum time of delivery to improve fetomaternal outcome. There are limited number of studies from northern India assessing the relationship between hypertensive disorders of pregnancy and retinopathy. This study was undertaken to bridge this gap. Methods: This was an observational cohort study undertaken in a tertiary hospital, 225 patients of preeclampsia coming to the department were identified and a structured proforma used to gather relevant information. All patients underwent fundoscopy and were classified into groups on the basis of fundal grade observed. The groups were compared in terms of clinicodemographic variables. Appropriate statistical tests were applied. Results: A total 68% patients had retinal changes of which the most common grade was grade 1 There was a significant rise in the mean systolic and diastolic blood pressure with increasing grade of fundal change. The (p-value 0.001). 65.5% of patients of preeclampsia without severe features (i.e. mild cases) had no retinopathy. None of these patients had grade 3 or 4 changes. In the patients of preeclampsia with severe features, 88.9% cases had varying degrees of retinopathy. Conclusions: As severity of preeclampsia increases, incidence of retinopathy also increases. Fundoscopy is a useful diagnostic aid and should be done to optimize fetomaternal outcome.